Physical radiofrequency adjuvant enhances immune responses to influenza H5N1 vaccination. Issue 3 (3rd February 2022) - Li, Zhuofan; Kim, Ki‐Hye; Bhatnagar, Noopur; Park, Bo Ryoung; Jeeva, Subbiah; Jung, Yu‐Jin; Raha, Jannatul; Kang, Sang‐Moo; Chen, Xinyuan
Abstract: Pre‐pandemic influenza H5N1 vaccine has relatively low immunogenicity and often requires high antigen amounts and two immunizations to induce protective immunity. Incorporation of vaccine adjuvants is promising to stretch vaccine doses during pandemic outbreaks. This study presents a physical radiofrequency (RF) adjuvant (RFA) to conveniently and effectively increase the immunogenicity and efficacy of H5N1 vaccine without modification of vaccine preparation. Physical RFA is based on a brief RF treatment of the skin to induce thermal stress to enhance intradermal vaccine‐induced immune responses with minimal local or systemic adverse reactions. We found that physical RFA could significantly increase H5N1 vaccine‐induced hemagglutination inhibition antibody titers in murine models. Intradermal H5N1 vaccine in the presence of RFA but not vaccine alone significantly lowered lung viral titers, reduced body weight loss, and improved survival rates after lethal viral challenges. The improved protection in the presence of RFA was correlated with enhanced humoral and cellular immune responses to H5N1 vaccination in both male and female mice, indicating no gender difference of RFA effects in murine models. Our data support further development of the physical RFA to conveniently enhance the efficacy of H5N1 vaccine.